2013
DOI: 10.1055/s-0033-1358583
|View full text |Cite
|
Sign up to set email alerts
|

Probable Correlation between Temporomandibular Dysfunction and Vertigo in the Elderly

Abstract: Introduction Temporomandibular disorder (TMD) covers a variety of clinical problems, and some epidemiologic studies have tried to indicate mechanisms of interaction and association between vertigo and TMD, but this topic still is controversial. Objective To assess the presence of vertigo in elderly patients associated with TMD. Methods A cross-sectional study was conducted with the inclusion of elderly individuals who lived independently. TMD was assessed by dental evaluation and vertigo was verified by medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…A relevant percentage of patients (19.8%) also reported new-onset vertigo, confirming that balance disorders are possible complications of TMD [8,17]. Although the pathophysiological mechanisms underlying the link between vertigo and TMD are poorly understood, possible hypotheses described in the literature include arterial constriction in the temporal region and irritation of the auriculotemporal nerve due to dysfunction of the masticatory muscles [8,18].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A relevant percentage of patients (19.8%) also reported new-onset vertigo, confirming that balance disorders are possible complications of TMD [8,17]. Although the pathophysiological mechanisms underlying the link between vertigo and TMD are poorly understood, possible hypotheses described in the literature include arterial constriction in the temporal region and irritation of the auriculotemporal nerve due to dysfunction of the masticatory muscles [8,18].…”
Section: Discussionmentioning
confidence: 84%
“…Parafunctional habits could contribute to the onset and progression of painful TMD due to the great sensitization of afferent nociceptors caused by persistent mechanical stimuli [6]. Some studies have also shown a significant relationship between TMD and otological symptoms [7][8][9], possibly due to excessive mechanical forces on the discomalleolar ligament or direct pressure on the auriculotemporal nerve [10]. In particular, TMDs have been suggested to be a risk factor for the development of severe tinnitus [11].…”
Section: Introductionmentioning
confidence: 99%
“…The significant relationship between TMD and vertigo has shown the importance of defining the risk factors for vertigo. Weak positioning of the mandibular condyle can cause ear pain, ringing in the ears, and dizziness [23].…”
Section: Discussionmentioning
confidence: 99%
“…No. 39, Vol 2, 40-55 2023I ISSN:2215 problemas clínicos asociados con la articulación temporomandibular, los músculos masticatorios y otras estructuras circundantes como las estructuras auriculares asociadas (Marchiori, 2014. ) Recientemente, la Academia de Dolor…”
Section: P 42unclassified